A chart of the Island of Newfoundland and the coast of Labrador with part of Greenland - Anspach, Lewis Amadeus, 1770-1823 ([London], 1819)
Black and white. Prime meridian Greenwich. North arrow. Bar scales in nautical miles and British statute miles. Shows underwater features. "Drawn and engraved expressly for the Reverend L.A. Anspach's History of Newfoundland" (title). -- Includes inset: Description of Terra de Baccalaos or Newfoundland. by Ortelio the Spanish Geographer in the year 1587.